Social Protection in a Crisis : Argentina's Plan Jefes y Jefas - Galasso, Emanuela; Ravallion, Martin (World Bank, Washington, DC, 2014)
The authors assess the impact of Argentina's main social policy response to the severe economic crisis of 2002. The program aimed to provide direct income support for families with dependents, for whom the head had become unemployed due to the crisis. Counterfactual comparisons are based on a matched subset of applicants not yet receiving the program. Panel data spanning the crisis are also used. The authors find that the program reduced aggregate unemployment, though it attracted as many people into the workforce from inactivity, as it did people who would have been otherwise unemployed. While there was substantial leakage to formally ineligible families, and incomplete coverage of those eligible, the program did partially compensate many losers from the crisis, and reduced extreme poverty.